Problems faced by English Teachers in Doimukh, Arunachal Pradesh - Pertin, Cheenang; Singh, Vivek (THE PRIMARY TEACHER, 2018)
Teaching and learning is a two–way process. Hence, feedback of teaching– learning experiences must highlight the needs and expectations of both learners and teachers. It is often observed that school managements and parents tend to put the onus onto teachers, especially, English language teachers, if students are unable to understand topics being taught in classrooms. Learning, especially, language learning, does not take place by confining children within the four walls of a classroom or by merely making them memorise some grammatical rules. There are other factors as well that contribute to language learning and competence, which only a language teacher would be able to shed light on. The present study tries to identify some of the common problems faced by English language teachers in teaching the language in the Doimukh area of Arunachal Pradesh. A face-to-face survey was conducted to identify the problems being faced by English language teachers in the area.